Pengaruh Persepsi Masyarakat Disabilitas terhadap Minat Menabung di Bank Syari'ah: Studi Kasus Masyarakat Disabilitas Pada Organisasi PPDI Cabang Kota Tebing Tinggi - Husein, Ali; Sihotang, Mutiah Khaira (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The banking world has developed a lot, one of which is shari'ah banks, these developments and growth can be one of the solutions in helping the economy of people in Indonesia. However, currently many levels of society, including disabilities, do not understand the concept of Islamic banks well. This is the background of researchers conducting research on the influence of perceptions of people with disabilities on interest in saving at Bank Syari'ah, especially in Tebing Tinggi City. The population in this study is people with disabilities in the Tebing Tinggi city branch PPDI organization which amounted to 266 people so that the number of samples of this study was 25% of the entire population, which is 67 people. Based on the results of the study that the perception of people with disabilities has an influence on the interest in saving with a t-count value greater than the t-table, which is 12.458 > 2.002 and a significant value smaller than the probability value of 0.000 < 0.005.